2011
DOI: 10.1007/s00436-011-2594-y
|View full text |Cite
|
Sign up to set email alerts
|

Anthelmintic effect of a methanol extract of Bombax malabaricum leaves on Paramphistomum explanatum

Abstract: Bombax malabaricum (family Bombacaceae) is used as anthelmintic in traditional system of medicine in Southern Punjab of Pakistan. The objective of this study was to evaluate the anthelmintic activity of the methanol extract of B. malabaricum leaves (MEBM). Live parasites (trematode: Paramphistomum explanatum) were collected from buffalo in 0.9% phosphate-buffered saline. It was incubated in Petri dishes at 37 ± 1°C in media containing either no extract (control) or MEBM, the test drug at 10, 25, 50, and 100 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 19 publications
3
27
0
Order By: Relevance
“…Kundu et al (2012) revealed the broad wormicidal (paralysis and death) in vitro activity of Cassia alata, Cassia angustifolia and Cassia occidentalis (crude ethanol extracts at 10, 20 and 40 mg/ml) against various parasites (trematode Catatropis spp., cestode Raillietina tetragona and nematode H. gallinarum) collected from domestic fowl. The observed effects could be attributed to the large amount of alkaloids, flavonoids, glycosides, tannins that these plants are known to contain (Hossain et al, 2012). Another study revealed similar effects for the ethanolic extract of the leaves of Eupatorium triplinerve (50 and 100 mg/ml) and of the rhisome of Alpinia galangal (100 mg/ml) against A. galli.…”
Section: In Vitro Studiessupporting
confidence: 54%
“…Kundu et al (2012) revealed the broad wormicidal (paralysis and death) in vitro activity of Cassia alata, Cassia angustifolia and Cassia occidentalis (crude ethanol extracts at 10, 20 and 40 mg/ml) against various parasites (trematode Catatropis spp., cestode Raillietina tetragona and nematode H. gallinarum) collected from domestic fowl. The observed effects could be attributed to the large amount of alkaloids, flavonoids, glycosides, tannins that these plants are known to contain (Hossain et al, 2012). Another study revealed similar effects for the ethanolic extract of the leaves of Eupatorium triplinerve (50 and 100 mg/ml) and of the rhisome of Alpinia galangal (100 mg/ml) against A. galli.…”
Section: In Vitro Studiessupporting
confidence: 54%
“…Various studies on in vitro and in vivo anti-trematodal activity of medicinal plants viz., alcoholic extract of Allium sativum and Piper longum [58], Balanites aegyptica [17], bark of Prosopis cineraria [18], Plumbagin on Fasciola gigantica and Paramphistomum cervi [37,59], 50 medicinal plants against Schistosoma mansoni and Echinostoma caproni used in Côte d' Ivoire [16], Bombax malabaricum leaves against Paramphistomum explanatum [15], Dregea volubilis leaves against Paramphistomum explanatum [60], Artemisia annua, A.absinthium, A.siminatriloba and Fumaria officinalis against adult Schistosoma mansoni, Fasciola hepatica and Echinostoma caproni in vitro [14], Aegle marmelos, Andrographis lineata, A.paniculata, Cocculuc hirsutus, Eclipta prostrata and Tagetes erecta against Paramphistomum cervi [13], Flemingia estita root tuber against Paramphistomum sp. [9].…”
Section: Discussionmentioning
confidence: 99%
“…The trials to using plants as anthelmintic remedies go back to older methods of the pre chemotherapeutical periods; however they have become more and more important today [8]. Several plants have been tested for their anthelmintic efficacies [9][10][11][12][13][14][15][16][17][18], against trematode infection. To date, there has been no literature cited to show the anthelmintic property of Marattia fraxinea Sm., lower vascular cryptogamic plants scientifically investigated to establish whether or not they have antitrematodal properties in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…The medicinal uses of Pteridophytes have been viably reported (Benjamin & Manickam 2007;Benniamin 2011). The anti-trematodal property of flowering plants has been reported worldwide (Hossain et al 2012;Alvarez-Mercado et al 2015); Blakemore et al (1964) and Amritpal Singh (2011) reported on the anthelmintic property of ferns. Kalpana Devi et al (2016) reported on the anti-trematodal property of Blechnum orientale against Gastrothylax crumenifer.…”
Section: Introductionmentioning
confidence: 99%
“…The origin of many effective drugs is found in traditional medicine practices and has made several researchers to undertake studies for evaluating folklore medicinal plants on their proclaimed anthelmintic efficacy (Mehlhorn et al 2011). Use of medicinal plants and studies on the chemistry and pharmacology of natural products have grown considerably in the second half of twentieth century (Hossain et al 2012). Therefore, there has always been a need to find new anthelmintic drugs because current drugs do not control all parasitic infections well.…”
Section: Introductionmentioning
confidence: 99%